Karakteristik Kue â€œLekunâ€ Khas Maumere Timur Ditinjau Dari Jenis Kemasan Dan Lama Penyimpanan - Maria Intan Claudia Yatub; A A Made Semariyani; Ni Made Ayu Suardani Singapurwa (GEMA AGRO, 2021)
â€œLekunâ€ cake is a traditional East Maumere cake that is specially made during engagement ceremonies to weddings or mourning ceremonies (Lodo Huer). â€œLekunâ€ cake has the potential to be used as souvenirs at this time. However, the "lekun" cake experienced changes in texture hardness and fungal contamination during storage for more than one day at room temperature. This study aims to determine which type of packaging produces the best characteristics of "lekun" cakes and to determine the shelf life of "lekun" cakes packaged in primary packaging (bamboo, dried banana leaves, corn husks, polypropylene plastic) and secondary packaging (besek) at room temperature. The design used was a completely randomized design with two factors and three replications, the first factor was the type of packaging consisting of four treatments, namely bamboo and plastic packaging, dried banana leaf packaging and besek, corn husks and besek packaging, and polypropylene plastic packaging and plastic bags. . The second factor was storage time which consisted of two treatments, namely the second day and the fourth day. Observations were made objectively covering water content, fat content, protein content, ash content, carbohydrate content, acidity (pH), total anthocyanin content, texture hardness level and subjectively covering color, taste, aroma, texture, overall acceptance and visual test. mold growth. The results showed that bamboo as primary packaging and besek as secondary packaging produced the best "lekun" cake characteristics. The shelf life of â€œlekunâ€ cakes packaged in bamboo and corn husks is two days, while the dried banana leaves and polypropylene plastic packaging is one day at room temperature